Epstein–Barr Virus Prevalence at Diagnosis and Seroconversion during Follow-Up in Pediatric Inflammatory Bowel Disease - Jennifer Bachmann (MDPI AG, 2021)
Primary Epstein–Barr virus infection in pediatric patients with inflammatory bowel disease during immunomodulation with thiopurines has been associated with increased risk for malignancies or hemophagocytic lymphohistiocytosis. We determined Epstein–Barr virus (EBV) seroprevalence at inflammatory bowel disease (IBD) diagnosis and seroconversion during follow-up in a large single center cohort of children with IBD. EBV serology results and patient characteristics were retrospectively retrieved from the hospital documentation system. EBV seronegative patients at IBD diagnosis were prospectively retested. We report on IBD patients with symptomatic active EBV infection and a complicated disease course, and those diagnosed with malignancy with respect to EBV status and drug exposure. Of 402 patients, 194 (48%) had available EBV serology results at time of IBD diagnosis at a median of 12 years (IQR 9–14 years). Thereof, 102 (53%) were EBV-positive. Of 92 EBV-negative patients, 66 were retested and 17% showed a seroconversion at a mean follow-up time of 4.3 years (SD 3 years). Three children treated with azathioprine experienced acute clinically relevant EBV infection 2, 2.5, and 4 years after IBD diagnosis, two developed signs of hemophagocytic lymphohistiocytosis. Three cases of malignancy occurred in the cohort, though none seemed to be triggered by EBV. In conclusion, almost 50% of pediatric IBD patients were EBV-naïve following diagnosis and may be at increased risk to develop severe EBV infection during immunosuppressive therapy, potentially associated with complications such as hemophagocytic lymphohistiocytosis or malignancy.